Physical Characteristics and Antioxidant Activity of Ice Cream Blend of Coconut Milk and Red Dragon Fruit Peel Extract - Teltje Koapaha; Tineke M. Langi; Riel J. J Umboh (Postgraduate, University of Mataram, 2025)
Coconut milk, which is rich in fat and protein, is used as a substitute for milk fat in making ice cream. Red dragon fruit skin contains antioxidants such as anthocyanins, flavonoids, and polyphenols, serving as a natural colorant and increasing the nutritional value of ice cream. This study aims to analyze the overrun, melting power, color and antioxidant activity of ice mixture of coconut milk and red dragon fruit peel extract. The research method used was a Completely Randomized Design (CRD) with four mixed proportion treatments: 100% coconut milk, 75% coconut milk and 25% red dragon fruit skin extract, 50% coconut milk and 50% red dragon fruit skin extract, 25% coconut milk and 75% red dragon fruit skin extract. Repetition was done three times in each treatment. Data analysis used analysis of variance (ANOVA), then BNT test if there were significant differences. The results showed that the overrun of ice cream ranged from 36.1% - 51.2%; melting power of ice cream 18.3 - 24.3 minutes; ice cream color with color grade of ice cream brightness value (L) 65.7-91.3; a value (red/green) -0.36 - 40.6s and b value (yellow/blue) -0.4 - 0.96. The antioxidant activity of the ice cream varied between 37.1 - 541.6 ppm. In conclusion, mixed ice cream of red dragon fruit peel extract and coconut milk has the potential to be developed as a nutritious processed food product, because it has antioxidant activity with good physical characteristics. This study also provides contextual scientific material that can be integrated into science learning about antioxidants and food technology.